MEMBER CARD SEBAGAI ALAT PEMBAYARAN DI ALFAMART KOMYOS SUDARSO PERSPEKTIF HUKUM ISLAM - Nursafitri, Melisa; Ma'u, Dahlia Haliah; Hakimah, Nur (Al-Aqad, 2023)
This study aims to determine the practice of buying and selling using a member card at Alfamart Komyos Sudarso from the perspective of Islamic law. This study used a qualitative research method with a type of field research and a normative-empirical research paradigm. The data sources included interviews with Alfamart employees and consumers who use a member card. Secondary data was obtained through primary legal materials, namely KHES, the Quran, and Hadith, and secondary legal materials such as books, journals, and scientific works. Data collection techniques included observation, interviews, and documentation. The findings of the study: 1) The practice of buying and selling using a member card at Alfamart Komyos Sudarso is such that consumers who want to register as members must fulfill certain conditions. Buyers can use the card, show it to the cashier, and scan the barcode. Consumers can earn points and discounts. Each consumer who uses this card will receive 1 point valued at IDR 200.00. 2) The Islamic legal review of the buying and selling using a member card at Alfamart Komyos Sudarso explains that the use of this card does not involve coercion because consumers who wish to register do so voluntarily. In buying and selling, it is necessary to meet the principles of trading so that transactions follow Islamic law.